Blockchain applications and management: a multidisciplinary analysis - Rosli, Athirah; Hassan, Suhaidi; Omar, Mohd Hasbullah; Sajat, Mohd Samsu; Mahmod Attar Bashi, Zainab Senan; Mohd Zaini, Khuzairi (IEEE, 2025)
Blockchain technology has emerged as a transformative force across multiple sectors, including education, health-care, real estate, maritime, and financial services. This paper explores its diverse applications and management within these fields, highlighting blockchain's ability to enhance transparency, security, and efficiency. In education, blockchain streamlines credential verification and academic records management, ensuring authenticity and reducing fraud. In healthcare, it secures patient data management and improves drug traceability, addressing critical issues of data privacy and regulatory compliance. The real estate sector benefits from blockchain through simplified property transactions and enhanced transparency, while the maritime industry leverages it to reduce paperwork and streamline customs processes, improving port operations and cargo handling. Financial services utilize blockchain for cryptocurrencies, decentralized finance, and cross-border payments, demonstrating secure and transparent transactions. Despite these advantages, challenges such as data privacy concerns, regulatory hurdles, and system integration persist. Successful case studies, like Malaysia's E-Skrol initiative and the University of Nicosia's blockchain-based diplomas, offer valuable insights for broader adoption. This paper identifies key issues in blockchain adoption across multiple sectors, including challenges with data privacy, regulatory hurdles, system integration, and the need for improved scalability, energy efficiency, and interoperability with emerging technologies like IoT and AI